CI-VI-LIZE 2024: Traces of Civilization and Art Reflecting Social-Environmental Changes - Kanrattanasutra, Pasutt (DEC Journal : Art and Design, 2025)
This article aims to (1) study and explore the relationship between ecological sustainability and the development of human civilization, (2) analyze the semiotic meaning and significance of the sculpture CI-VI-LIZE 2024 in the context of the relationship between civilization development and environmental sustainability, and (3) demonstrate the role of contemporary art in raising awareness and stimulating criticism about environmental and sustainability issues in today’s society. This research employs qualitative research methodology through semiotic interpretation analysis, analyzing the meaning of symbols and materials appearing in the sculpture CI-VI-LIZE 2024 to understand its connotative meaning, reviewing literature and research related to the relationship between art, society, and environment, including concepts of sustainable development and the role of art in creating social change, and comparative case studies of CI-VI-LIZE 2024 with other contemporary artworks related to environmental and sustainability issues. Research findings (1) Reveal the relationship between ecological sustainability and human civilization development, showing that many ancient civilizations collapsed due to mismanagement of resources, while the industrial era accelerated environmental destruction, though humans have the potential to adapt through sustainable development concepts, (2) The semiotic analysis of CI-VI-LIZE 2024 shows how it questions the direction of civilization through its name and materials that blend natural elements with industrial products; its structure resembling ancient ruins combined with contemporary technology warns of collapse risks if humans neglect the environment, and (3) Contemporary art’s role in raising awareness about environmental issues is demonstrated as CI-VI-LIZE 2024 creates aesthetic experiences that stimulate awareness of environmental problems, provides a space for sustainability discussions, and builds networks driving change through the integration of historical, sociological, and ecological dimensions.